PTU-069 Effect of Adalimumab on Patients with Moderate to Severe Ulcerative Colitis in UK Clinical Practice Setting: Results from Inspirada. (17th August 2016) - Irving, P; Cummings, F; Bloom, SL; Lazar, A; Robinson, AM; Pappalardo, BL; Bereswill, M; Skup, M; Chen, N; Finney-Hayward, T; Wang, S; Thakkar, RB; et al.
Abstract : Introduction: Limited real world data are available regarding the effects of adalimumab (ADA) on UK patients with moderate to severe ulcerative colitis (UC). Methods: INSPIRADA was a single-arm, multi-country, open-label study that evaluated the effect of ADA on patients with UC treated according to usual clinical practice. Adults with active moderate to severe UC who failed immunosuppressive therapies and experienced rectal bleeding within 7 days of baseline (BL) were enrolled. Prior use of anti-TNF was allowed. Clinical outcomes included Simple Clinical Colitis Activity Index (SCCAI) response (a decrease ≥2 points compared to BL) and remission (SCCAI ≤2). HRQoL (EQ-5D-5L and SIBDQ), treatment satisfaction with medication (TSQM), and work productivity and activity impairment (WPAI) were measured from BL to week 26. Direct medical costs (excluding ADA costs) were estimated using 2014 UK National Health Service reference costs. Indirect costs were based on the WPAI using average weekly earnings from the 2014 UK Annual Salary Survey of Hours and Earnings. Change (defined as 6 mo after start of ADA vs 6 mo before) in resource use and costs were calculated. Data for the intent-to-treat population in UK were analysed. Missing data were imputed using last observation carried forward. Results: Data from 90 UK patients (58% male, mean age 39 yrs) were analysed. Mean SCCAI at BL was 8.2. At week 2, 74% achieved SCCAI response and 21% achieved SCCAI remission. At week 8, 73% achieved SCCAI response, 40% in remission and 49% had no blood in stool. At week 26, 66% achieved SCCAI response, 42% in remission and 51% had no blood in stool. Significant improvements, as early as within 2 weeks, in SIBDQ (19.5 points, p < 0.001), EQ-5D-5L (0.12 index score and 20.5 VAS points, both p < 0.001), 3 of 4 WPAI domains (−31%, −32%, −32%, all p < 0.001), and 3 of 4 TSQM domains (18%, 23%, 29%, all p < 0.001) occurred from BL to week 26. Significant decreases in UC-related medical costs (−£1857, p < 0.001), all-cause direct costs (−£1613, p < 0.001), and UC-related direct + indirect costs (−£6001, p < 0.001) occurred 6 mo after starting ADA compared to 6 mo before starting ADA. Conclusion: Real world rates of response, remission and improvements in HRQoL with ADA for UK patients with moderate to severe UC were clinically meaningful. ADA improved work productivity, increased patient satisfaction with therapy and reduced health care associated costs for these patients in the UK. Disclosure of Interest: P. Irving Grant/research support from: AbbVie; Falk; Ferring; Genentech/Roche; Hospira; Merck; Pharmacosmos; Shire; Takeda; Tillotts; Topivert; Vifor and Warner Chilcott, Conflict with: Advisor/invited lecturer for: AbbVie; Falk; Ferring; Genentech/Roche; Hospira; Merck; Pharmacosmos; Shire; Takeda; Tillotts; Topivert; Vifor and Warner Chilcott, F. Cummings Conflict with: Advisor/lectures for: Takeda, Abbvie, MSD, Biogen, Napp, Hospira, Janssen, S. Bloom Conflict with: Advisor/lectures for: Takeda, Tillotts, Abbvie, MSD, Pharmacosmos, Vifor, Johnson and Johnson, A. Lazar Shareholder of: AbbVie, Employee of: AbbVie, A. Robinson Shareholder of: AbbVie, Employee of: AbbVie, B. Pappalardo Shareholder of: AbbVie, Employee of: AbbVie, M. Bereswill Shareholder of: AbbVie, Employee of: AbbVie, M. Skup Shareholder of: AbbVie, Employee of: AbbVie, N. Chen Shareholder of: AbbVie, Employee of: AbbVie, T. Finney-Hayward Shareholder of: AbbVie, Employee of: AbbVie, S. Wang Shareholder of: AbbVie, Employee of: AbbVie, R. Thakkar Shareholder of: AbbVie, Employee of: AbbVie, S. Travis Grant/research support from: AbbVie; Asahi; Boehringer Ingelheim; BMS; Cosmo; Elan; Ferring; FPRT Bio; Genentech/Roche; Genzyme; Glenmark; GW Pharmaceuticals; Lilly; Merck; Novartis; Novo Nordisk; Ocera; Pfizer; Shire; Santarus; SigmoidPharma; Synthon; Takeda; Tillotts; Topivert; Trino Therapeutics with Wellcome Trust; UCB Pharma; Vertex; VHsquared; Vifor; Warner Chilcott and Zeria, Conflict with: Advisor or paid instructor for: AbbVie; Asahi; Boehringer Ingelheim; BMS; Cosmo; Elan; Ferring; FPRT Bio; Genentech/Roche; Genzyme; Glenmark; GW Pharmaceuticals; Lilly; Merck; Novartis; Novo Nordisk; Ocera; Pfizer; Shire; Santarus; SigmoidPharma; Synthon; Takeda; Tillotts; Topivert; Trino Therapeutics with Wellcome Trust; UCB Pharma; Vertex; VHsquared; Vifor; Warner Chilcott and Zeria. All advisory boards were suspended Q1 2012–14 while President of ECCO